Collectivisation in Lithuania 1947–1952: Decisions and Control by the CC of the All-Union CP - Pocius, Mindaugas (Genocidas ir rezistencija, 2018)
Referring to documents from the Russian State Archive of Socio-Political History and other sources, the article aims to reveal little-known aspects of the collectivisation policy of the All-Union Communist Party (Bolsheviks) Central Committee and the Communist Party of Lithuania (Bolsheviks) Central Committee in Lithuania, showing the issues that have received constant attention and control from the ACP(B) CC, the decisions taken and the cooperation with the CPL(B) CC.
Keywords: Lithuania; soviet occupation; communist party; collectivisation